Someone Knows - Scottoline, Lisa (New York : G.P. Putnam's Sons, an imprint of Penguin Random House LLC, 2019)
Haunted by her role in a covered-up prank gone wrong twenty years earlier, Allie returns to her hometown for a friend's funeral and resolves to uncover the truth.
Keywords: Secrecy -- Fiction; Practical jokes -- Fiction; Thrillers (Fiction); Mystery fiction; Detective and mystery fiction